Turbulência de Ondas em condensados de Bose-Einstein - Santos Filho, Marcos Alberto Gonçalves dos (2018)
In this work we used as a starting point the theory developed by Zakharov and Nazarenko for treating wave turbulence in systems with weak non linearity such as atomic Bose-Einstein condensates with low enough temperature to be described by the Gross-Pitaevskii model. After we obtained the kinetic equation for the condensate and extracted the out of equilibrium stationary solution, the so called Kolmogorov-Zakharov cascates, we set course to our objective of demonstrating that it is possible to conciliate this solutions of the kinetic equation with the hydrodynamical properties of the condensate. In order to do that we calculated the correlation function of the condensate current for both the weak condensate state and the strong condensate state using the respective wave turbulence cascates. With this result we have shown that there is a connection between the arising of wave turbulence and the variables related to the hydrodynamical turbulence of this system, which are essential for the comprehension of quantum turbulence as a whole.